Characterization of the Intra-tumoral B Cell Immunoglobulin Repertoire Is of Prognostic Value for Esophageal Squamous Cell Carcinoma - Wang, Zhizhong; Cheng, Zhenguo; Lu, Shuangshuang; Chard Dunmall, Louisa S.; Wang, Jun; Guo, Yongjun; Wang, Yaohe (Frontiers in Immunology, 2022)
Esophageal Squamous Cell carcinomas (ESCC) is a highly heterogeneous malignancy that is among the leading cause of cancer-related death worldwide. B cells play pivotal roles in the immune defense system and cancer progression and regression, yet the repertoire of tumor infiltrating B cells (TIBs) and its association with clinical outcome remains unexplored in ESCC. Here we collected bulk RNA-seq sequencing data from 119 ESCC tumors and matched adjacent normal samples to delineate the B cell repertoire. We found that ESCC is more heavily infiltrated by B cells and plasma cells compared to activated T cells. The immunoglobulin heavy chain variable region (IGHV) gene usage was remarkably biased and IGHV3-74 was under-represented in ESCC tumors. The TIBs showed a more oligoclonal profile along with widespread clonal expansion and IgG subclass switch events (CSRs). Survival analysis revealed several unexpected associations between tumor infiltrating B cells and prognosis. Higher levels of immunoglobulin expression (IGH), CD138 expression, IGH to MS4A1 ratio, CSR events and clone diversity are all associated with better survival. Notably, we found that the abundance of CD20-negative IgG2-producing plasma cells has a strong positive effect on overall survival with a hazard ratio (HR) of 0.40 (log-rank p: 0.002). Combing molecular subtyping, the IgG2-producing plasma cells could stratify high-risk patients more accurately with a HR of 0.253 (log-rank p: 0.0006). The direct link between protective B cell populations and ESCC prognosis provides biomarkers for high-risk patient selection and holds great promise for developing strategies for immunotherapy targeting B cells in ESCC patients.